NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muslikhin Muslikhin (UIN Fatmawati Sukarno Bengkulu, 2019)
This research to description result Observationaling to conclude that: character point instillings most ridicules into 3 groups. a ). Character education points already walks properly which is relegius’s character point, creativity character point and independence character point, b ) character education points a new one executed at sufficiently which is sincerity, discipline and democracy, c ) character education points that was performed or still so minim which is tolerance, hard-earned, inquiring taste, nationalistic spirit, country love, pricing achievement, brotherly/comunicating, placating love, like to read, environmental care, social care and responsible. Meanwhile bases observation, Education learning process Islam that gets bearing with education point instillings characters on student, get concluded that teacher third that was optimal deep instilling assesses character education on islam education subject.